Von Causenflickern und Rittern der Rechte Juristenkritik und Juristenideal in der Frühen Neuzeit - Flechsig, Katharina (Universitätsverlag Göttingen, 2021)
In the period between the 16th and the 18th century, there was an unprecedented increase in statements criticising lawyers. They characterised judges and advocates in particular as greedy, corruptible and perverting the course of justice. In parallel, the image of an ideal jurist was drawn in the sources in the sense of a counter-draft. At the same time, in the early modern period not only did the field of activity of the legal experts change in the legal system itself, but also their role in the social structure. The development, use and content of both ideal concepts and patterns of criticism are closely related to these changes. The negotiation of professional legal ethics that took place in the early modern period is thus a component of the professional history of judges and lawyers.